A new antibiotic selectively kills Gram-negative pathogens - Imai, Yu (Nature, 2019)
The current need for novel antibiotics is especially acute for drug-resistant Gram-negative pathogens(1,2). These microorganisms have a highly restrictive permeability barrier, which limits penetration of most compounds(3,4). As a result, the last class of antibiotics acting against Gram-negative bacteria was developed in the 60s(2). We reason that useful compounds can be found in bacteria that share similar requirements for antibiotics with humans, and focus on Photorhabdus symbionts of entomopathogenic nematode microbiomes. Here we report a new antibiotic that we name darobactin, from a screen of Photorhabdus isolates. Darobactin is coded by a silent operon with little production under laboratory conditions, and is ribosomally synthesized. Darobactin has an unusual structure with two fused rings that form post-translationally. The compound is active against important Gram-negative pathogens both in vitro and in animal models of infection. Mutants resistant to darobactin map to BamA, an essential chaperone and translocator that folds outer membrane proteins. Our study suggests that bacterial symbionts of animals harbor antibiotics that are particularly suitable for development into therapeutics.